Effects on bacon quality of feeding increasing glycerol and dried distillers grains with solubles to finishing pigs - B L Goehring; Terry A Houser; Joel M DeRouchey; Melvin C Hunt; Michael D Tokach; Steven S Dritz; B M Gerlach; Robert D Goodband; Jim L Nelssen; John A Unruh (Kansas Agricultural Experiment Station Research Reports, 2010)
A total of 84 barrows (PIC 337 x 1050, initially 68.3 lb) were fed a corn-soybean meal-based diet with added dried distillers grains with solubles (DDGS; 0 or 20%) and increasing glycerol (0, 2.5, or 5%) to determine the effects on belly quality. Criteria that were evaluated included: belly length, thickness, firmness, and slice yield; proximate and fatty acid analyses; iodine values; and sensory characteristics. There were no (P>0.08) DDGS x glycerol interactions on any criteria measured. Inclusion of 20% DDGS in the diet decreased belly firmness (P<0.04), as measured by the belly flop test (fat-side down method). Twenty percent DDGS decreased (P<0.01) the percentage of myristic acid, palmitic acid, palmitoleic acid, stearic acid, oleic acid, vaccenic acid, total saturated fatty acids, and total monounsaturated fatty acids. In contrast, 20% DDGS increased (P<0.01) the percentage of linoleic acid, Î±-linolenic acid, eicosadienoic acid, total polyunsaturated fatty acids, unsaturated:saturated fatty acid ratios, polyunsaturated:saturated fatty acid ratios, and iodine values. The inclusion of 0, 2.5, and 5% glycerol in swine diets did not affect any measured criteria in this study. In conclusion, feeding DDGS at a level of 20% decreased belly firmness and changed the fatty acid profile; however, it did not affect belly processing or sensory characteristics. Glycerol fed at 2.5 or 5.0% did not affect belly quality, fatty acid profile, or sensory characteristics of bacon.; Swine Day, Manhattan, KS, November 18, 2010
Keywords: Swine Day; 2010; Kansas Agricultural Experiment Station contribution; no. 11-016-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1038; Swine; Belly quality; Dried distiller grains with solubles; Glycerol